Peculiarities of Environmental Expertise in Solving Environmental Problems - Shayusupova Lobar Rikhsievna (International Journal on Integrated Education, 2022)
This article is devoted to the issues of topical measures for environmental protection and rational use of natural resources, where special attention is paid to the role of environmental expertise in ensuring environmental safety. The list of the main problems of ecological disaster is given, definitions of ecological expertise are given, the history of the formation of environmental impact assessment. In particular, examples of the experience of reclamation of landscapes disturbed by industry are considered. The article discusses the goals and objectives of environmental expertise on the basis of the Law “On Environmental Expertise”, as well as the principles of environmental expertise.